Autophagy-associated signal pathways of functional foods for chronic diseases - Jinfeng Xie; Jiling Liang; Ning Chen (Food Science and Human Wellness)
Functional foods, namely as natural or processed foods containing bioactive compounds, can provide health-promoting effects beyond basic nutrition, or offer the prevention or supplementary treatment of chronic diseases. The bioactive components in functional foods usually have pleiotropic effects, including antioxidant, anti-inflammatory, hypolipidemic, glycemic-regulating, cytoprotective, and neuroprotective functions. Autophagy is one of the highly conserved cellular processes for the clearance of aberrant components in eukaryotic cells, and plays an essential role in health promotion and prevention and treatment of a series of chronic diseases. Once the cells are in the stress environment, the induced autophagy will accelerate the clearance of cellular damaged or toxic protein aggregates or dysfunctional cellular organelles to maintain homeostasis in cells. In this article, we summarize several widely investigated bioactive components used as functional foods, such as resveratrol, epigallocatechin-3-gallate, curcumin and trehalose, with the regulatory function for autophagy during the intervention of chronic diseases, which will provide the references or novel thoughts for the development of functional foods with the modulation of autophagy. Keywords: Autophagy, Chronic diseases, Resveratrol, Epigallocatechin-3-gallate, Curcumin, Trehalose